Assessment of Cervical Spine Mobility in a Subjects with Rheumatoid Arthritis Associated with Neck Pain - Raj Mhatre; Poonam Patil (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background : Rheumatoid arthritis is an immunological mediated ,chronic inflammatory multisystemdisease which involves inflammation of peripheral joints along with involvement of haematological ,neurological and cardiovascular abnormality. Studies have shown that the involvement of cervical spineis common commonly affecting C1 and C21 due absence of intervertebral disc and synovial inflammationresulting in alteration in range of motion. Keeping in mind the inflammation and degeneration causesalteration in mobility . So that present study is conducted with the aim to find out proportion of alterationin mobility at the cervical spine range of motion in subjects with rheumatoid arthritis associated with neckpain.Methodology: An observational study was conducted in 33 patients at karad with study duration of 6 months.The inclusion criteria was the patient with rheumatoid arthritis any age and gender willing to participate.The outcome measures were goniometer and inch tape method of assessing the range of motion .Result: The results observational study suggest there is significant decrease in all movement of cervicaljoint with rotational components were hampered most around 26.36% loss of mobility for left rotation and26.12 % loss of mobility for right rotation followed by right lateral flexion , flexion, extension , right rotationand left rotation .Conclusion: the study concluded that rotational movements was more affected in a patients with rheumatoidarthritis associated with neck pain which is attributed to marked involvement of the C1 and C2 vertebraefollowed by other movements at the neck.